2014
DOI: 10.1055/s-0034-1367006
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-respiratory Fitness is Independently Associated with Cardio-Metabolic Risk Markers in Severely Obese Women

Abstract: Our data for the first time indicate that cardio-respiratory fitness is independently associated with cardio-metabolic risk markers in severely obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
1
10
0
1
Order By: Relevance
“…Putting this forward, we suggest that the degree of cardiorespiratory fitness plays a role in determining the degrees of metabolic alterations in severely obese subjects. Supporting this notion, we have recently reported on significant associations between cardiorespiratory fitness and distinct measures of glucose and lipid metabolism in a study population of 308 severely obese women [15]. In the present study, we tested whether similar associations can also be found in severely obese men.…”
Section: Introductionmentioning
confidence: 63%
“…Putting this forward, we suggest that the degree of cardiorespiratory fitness plays a role in determining the degrees of metabolic alterations in severely obese subjects. Supporting this notion, we have recently reported on significant associations between cardiorespiratory fitness and distinct measures of glucose and lipid metabolism in a study population of 308 severely obese women [15]. In the present study, we tested whether similar associations can also be found in severely obese men.…”
Section: Introductionmentioning
confidence: 63%
“…It is important to note that the cross-sectional nature of our study precludes to draw any conclusion on the cause-effect relationship between T2DM and reduced cardiorespiratory fitness. While T2DM could impair cardiorespiratory fitness it is also wellknown that low levels of physical activity -resulting in low cardiorespiratory fitness [37] -are associated with an increased risk for T2DM [28]. Indeed, we did not assess subjects' habitual physical activity which clearly represents a limitation of our study.…”
Section: Discussionmentioning
confidence: 91%
“…Data of cardiorespiratory exercise testing were available in 30 of the extracted matched T2DM/non-T2DM pairs. The same database was previously used to establish correction factors for metabolic equivalent calculations [27] and to assess the association of cardiorespiratory fitness with cardio-metabolic risk markers [28]. All patients gave their written informed consent for a scientific use of their clinical data and the study was approved by the local ethics committee of the canton of St. Gallen.…”
Section: Subjectsmentioning
confidence: 99%
“…It should be kept in mind that the metabolic consequences of abdominal obesity do not only depend on the extent of visceral fat accumulation but also on specific biological characteristics of visceral fat tissue such as adipocyte sizes and macrophages infiltration [43,44]. Also, other factors like cardio-respiratory fitness are well known to modulated the metabolic health state of obese subjects [45]. Therefore, it can be assumed that even the best measure of abdominal obesity will not provide sufficient information on the metabolic health state of a given individual obese subject which makes, in clinical practice, the measurement of relevant metabolic variables in blood samples necessary.…”
Section: Discussionmentioning
confidence: 99%